Doublesex regulates male-specific differentiation during distinct developmental time windows in a parasitoid wasp - Wang, Yidong; Rensink, Anna H.; Fricke, Ute; Riddle, Megan C.; Trent, Carol; van de Zande, Louis; Verhulst, Eveline C. (Insect biochemistry and molecular biology, 2022)
Sexually dimorphic traits in insects are subject to sexual selection, but our knowledge of the underlying molecular mechanisms is still scarce. Here we investigate how the highly conserved gene, Doublesex (Dsx), is involved in shaping sexual dimorphism in the model parasitoid wasp Nasonia vitripennis (Hymenoptera: Pteromalidae). First, we present the revised Dsx gene structure including an alternative transcription start, and two additional male NvDsx transcript isoforms. We show sex-specific NvDsx expression and splicing throughout development, and demonstrate that transient NvDsx silencing in different male developmental stages shifts two sexually dimorphic traits from male to female morphology, with the effect being dependent on the timing of silencing. In addition, we determined the effect of NvDsx on the development of reproductive organs. Transient silencing of NvDsx in early male larvae affects the growth and differentiation of the internal and external reproductive tissues. We did not observe phenotypic changes in females after NvDsx silencing. Our results indicate that male NvDsx is required to suppress female-specific traits and/or to promote male-specific traits during distinct developmental windows. This provides new insights into the regulatory activity of Dsx during male wasp development in the Hymenoptera. [Display omitted] •Two novel male-specific Doublesex isoforms are identified in Nasonia vitripennis.•Doublesex suppresses the default development of female-specific morphological traits in N. vitripennis males.•Doublesex regulates the development of smaller wing size in N. vitripennis males during distinct developmental windows.•Doublesex regulates genitalia tissue growth and differentiation during larval development.